Heart rate variability during auricular acupressure at the left sympathetic point on healthy volunteers: a pilot study - Trinh, Dieu-Thuong Thi; Le, Hoang-Linh Thi; Bui, Minh-Man Pham; Thai, Khac-Minh (Frontiers in Neuroscience, 2023)
Introduction This research is a pilot, single-blinded study investigating heart rate variability (HRV) during auricular acupressure at the left sympathetic point (AH7) in healthy volunteers. Methods There were 120 healthy volunteers with hemodynamic indexes (heart rate, blood pressure) within normal ranges, randomly divided into two groups AG and SG (in each group having a gender ratio 1:1, aged 20−29), to receive either auricular acupressure using ear seed (AG) or sham method using adhesive patches without seed (SG) at the left sympathetic point while lying in a supine position. Acupressure intervention lasted 25 min, and HRV was recorded by a photoplethysmography device–namely, Kyto HRM-2511B and Elite appliance. Results Auricular acupressure at the left Sympathetic point (AG) led to a significant reduction in heart rate (HR) (p < 0.05) and a considerable increase in HRV parameters demonstrated by HF (High-frequency power) (p < 0.05), compared to sham auricular acupressure (SG). However, no significant changes in LF (Low-frequency power) and RR (Respiratory rate) (p > 0.05) were observed in both groups during the process. Conclusion These findings suggest that auricular acupressure at the left sympathetic point may activate the parasympathetic nervous system while a healthy person is lying relaxed.